A Large Substernal Goiter that Extended to Both Sides of the Thorax. (5th November 2018) - Nakayama, Hirotaka; Goda, Motohiko; Kohagura, Kaori; Suganuma, Nobuyasu; Iwasaki, Hiroyuki; Yamazaki, Haruhiko; Toda, Soji; Masudo, Katsuhiko; Rino, Yasushi; Masuda, Munetaka
Abstract : Most substernal goiters can be managed through the transcervical approach, but a sternotomy is required in some cases. This report is about a large substernal goiter, which was resected via a transcervical and full sternotomy approach. The patient was a 57-year-old female, who visited our hospital for surgical treatment for a large substernal goiter. Computed tomography of the neck and chest revealed that the substernal goiter extended to both sides of the thorax and had compressed the trachea. We performed total thyroidectomy safely via a transcervical and full sternotomy approach. No postoperative complications occurred, except transient hypocalcemia. A histopathological examination did not reveal any malignancy, and the lesion was diagnosed as an adenomatous goiter. Most substernal goiters can be managed through the transcervical approach, but a full sternotomy is required when a substernal goiter extends to both sides of the thorax and/or has a larger diameter than the thoracic inlet or airway constriction is revealed. A full sternotomy provides excellent exposure and can help reduce the risk of complications, such as recurrent laryngeal nerve palsy and injuries to major blood vessels.